Improving pediatric pharmacy services in a primarily adult emergency department. (1st October 2021) - Hachem, Souheila N; Thomson, Julie M; Heigham, Melissa K; MacDonald, Nancy C
Abstract: Purpose: The American Society of Health-System Pharmacists (ASHP) and Pediatric Pharmacy Advocacy Group (PPAG) guidelines for providing pediatric pharmacy services in hospitals and health systems can be used to improve medication safety wherever pediatric patients receive care, including in the emergency department (ED). The purpose of this initiative was to improve compliance with these guidelines in a primarily adult ED. Methods: This quality improvement initiative was conducted in a level 1 trauma center ED between October 2019 and March 2020. The ASHP-PPAG guidelines were used to create practice elements applicable to the ED. An initial compliance assessment defined elements as noncompliant, partially compliant, fully compliant, or not applicable. Investigators identified interventions to improve compliance for noncompliant or partially compliant elements and then reassessed compliance following implementation. Data were expressed using descriptive statistics. This initiative was exempt from institutional review board approval. Results: Ninety-three ED practice elements were identified within the 9 standards of the ASHP-PPAG guidelines. At the initial compliance assessment, the majority (59.8%) of practice elements were fully compliant; however, various service gaps were identified in 8 of the standards, and 16 interventions were implemented to improve compliance. At the final compliance assessment, there was a 19.5% increase in full compliance. Barriers to achieving full compliance included technology restrictions, time constraints, financial limitations, and influences external to pharmacy. Conclusion: This quality improvement initiative demonstrated that the ASHP-PPAG guidelines can be used to improve ED pediatric pharmacy services in a primarily adult institution. The initiative may serve as an example for other hospitals to improve compliance with the guidelines.